2006
DOI: 10.1089/ars.2006.8.478
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB: A Stress-Regulated Switch for Cell Survival

Abstract: Nuclear factor-kappaB (NF-kappaB), a stress-regulated transcription factor belonging to the Rel family, has a pivotal role in the control of the inflammatory and the innate immune responses. Its activation rapidly induces the transcription of a variety of genes encoding cell adhesion molecules, inflammatory and chemotactic cytokines, cytokine receptors, and enzymes that produce inflammatory mediators. More recently, NF-kappaB activation has been connected with multiple aspects of oncogenesis, including the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 78 publications
2
104
0
1
Order By: Relevance
“…Disruption of aberrantly regulated survival signaling mediated by NFB has recently become an important task in the therapy of several chemoresistant and radioresistant cancers (15). IAPs are expressed at high levels in many tumors and have been reported to contribute to the resistance of cancers to therapy including resistance to radiotherapy (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of aberrantly regulated survival signaling mediated by NFB has recently become an important task in the therapy of several chemoresistant and radioresistant cancers (15). IAPs are expressed at high levels in many tumors and have been reported to contribute to the resistance of cancers to therapy including resistance to radiotherapy (45).…”
Section: Discussionmentioning
confidence: 99%
“…We identified that IR profoundly activates NFB in human NB cells (13,14), leading to induced radioprotection, and further that forced inhibition of NFB enhanced IR-induced cell death. To that end, disruption of aberrantly regulated survival signaling mediated by NFB has recently become an important task in the therapy of several chemoresistant/ radioresistant cancers (15). However, mechanistic orchestration of NFB after clinical doses of IR and its functional role in induced survival advantage and/or tumor recurrence is poorly understood.…”
Section: Neuroblastoma (Nb)mentioning
confidence: 99%
“…Interestingly, dexamethasone, which stimulates BHV-1 reactivation from latency, impairs NF-B signaling (22,86). Heat stress stimulates HSV-1 in vivo reactivation from latency in mice (68) and, like dexamethasone, impairs NF-B signaling (5,63). Thus, there appears to be a link between disrupting NF-B signaling, inducing apoptosis, and increasing the incidence of reactivation from latency.…”
Section: Discussionmentioning
confidence: 99%
“…In response to stress conditions such as infection and inXammation, an inactive form of NF-B present in the cytoplasm can be activated. Activated NF-B transcription factors have been associated with several features of tumorigenesis, including the proliferation, diVerentiation, and survival of lymphocytes (Piva et al 2006). In addition, there is evidence that NF-B activity plays an important role in the pathogenesis of activated B-cell-like DLBCL cell lines (Davis et al 2001;Alizadeh et al 2000), which is critical in lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%